Prices and Unit Labor Costs: A New Test of Price Stickiness - Argia M. Sbordone (Rutgers University, Department of Economics, 2001)
This paper investigates the predictions of a simple optimizing model of nominal price rigidity for the aggregate price level and the dynamics of inflation. I compare the model's predictions with those of a perfectly competitive, flexible price `benchmark' model (corresponding to the model of pricing assumed in standard real business cycle models), and evaluate how much the introduction of nominal rigidities improves the model's fit with the data. The model's predictions are derived using only the firms optimal pricing problem; taking as given the paths of nominal labor compensation, labor productivity, and output, I determine the implied path of prices predicted by the model. Because prices are not a stationary series, I present my results in terms of the predicted path of the price/unit labor cost ratio, where the parameters characterizing such paths are chosen to maximize the fit with the data. I find that while the evolution of prices relative to unit labor costs is quite different from what would be predicted by the flexible-price `benchmark' model, a simple model of nominal price rigidity delivers an extremely close approximation both of the price/unit labor cost ratio and of the inflation series, even under a very simple approach to the measurement of marginal costs.
Keywords: E31; E32; 330; Inflation; Phillips Curve; Unit Labor Cost